2009
DOI: 10.1007/s12630-009-9206-7
|View full text |Cite
|
Sign up to set email alerts
|

Preload or coload for spinal anesthesia for elective Cesarean delivery: a meta-analysis

Abstract: Background Hypotension following spinal anesthesia for Cesarean delivery is common. Fluid loading is recommended to prevent hypotension, but preload is often ineffective. In non-pregnant patients, coloading has been shown to better maintain cardiac output after spinal anesthesia. The purpose of this meta-analysis was to determine whether the timing of the fluid infusion, before (preload) or during (coload) induction of spinal anesthesia for Cesarean delivery, influences the incidence of maternal hypotension or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 26 publications
2
66
1
8
Order By: Relevance
“…On the other hand, Siddik-Sayyid et al [23] reported non-significantly higher incidence of hypotension (68% vs. 75%) and of severe hypotension (16% vs. 22%) with coloading compared to preloading. On contrary and in support of coloading, Banerjee et al [24] retrieved randomized controlled trials that compared a fluid preload with coload in patients undergoing spinal anesthesia for elective CS and reported non-significantly reduced frequency of hypotension with coloading.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Siddik-Sayyid et al [23] reported non-significantly higher incidence of hypotension (68% vs. 75%) and of severe hypotension (16% vs. 22%) with coloading compared to preloading. On contrary and in support of coloading, Banerjee et al [24] retrieved randomized controlled trials that compared a fluid preload with coload in patients undergoing spinal anesthesia for elective CS and reported non-significantly reduced frequency of hypotension with coloading.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies disapproved the fluid-loading regimen because no significant difference has been found with any given volume of fluid infused 11,16,27 . In Banerjee's systematic review, approximately 60% of patients still developed hypotension in both preloading and coloading regimens 20 . In our study, we observed about 42% of patients experience hypotension and the EV 50 of crystalloid was 13 mL.kg -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the coloading or postloading regimen has been proposed due to a much more effective role in decreasing the rate of hypotension [9][10][11][12] . However, Banerjee et al 20 reviewed on how the incidence of maternal hypotension in spinal anesthesia is still high -about 60% -regardless the fluid loading strategy used. In addition, neither of the conventional methods of fluid management -wether 'liberal' (2,000 mL per person) or 'restricted' (500 mL per person) -produced ideal effects on preventing hypotension and balancing circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Mercier et al 4 showed that loading fluid (coloading) at the time of administering the intrathecal local anesthetic may be a physiologically more appropriate and better approach as the maximal effect of coloading can be achieved during the time of the block. Banerjee et al, 6 in their meta-analysis,…”
Section: Blood Pressure Responsementioning
confidence: 99%
“…5,8 Fluid coloading appears to be more physiological and rational approach as the maximal effect can be achieved at the time of onset of the block. 6 Recently, few studies have been conducted which indicate that coloading may be equally effective as preloading with colloid. 7,8 Central venous pressure monitoring reflects the volume load in the circulatory system.…”
Section: Introductionmentioning
confidence: 99%